Optimising Results of Nasal Tip Rotation Applying Combination of Nasolabial Angle and Lip–Columellar Angle in Tandem in Patients Operated by “Cock-up” Alar Cartilage Flaps Technique - Uday Bhat; Amit Ratanlal Peswani; Snehjeet Wagh; Rohit Mishra; Tarush Gupta; Amresh Baliarsing (Indian Journal of Plastic Surgery)
Background Setting the angle of tip rotation is of utmost importance in achieving satisfactory results in rhinoplasty. Conventionally the upward rotation of the tip requires shortening of the septum by caudal resection and shortening of the lateral walls by cephalic trim of the alar cartilages. The results are usually assessed subjectively. We describe the use of objective parameters to ensure accuracy of nasal tip rotation in patients operated with “cock-up” alar cartilage flaps, a modification of the cephalic trim. Methods Fifteen patients with a long nose having adequate width of lateral crura, desiring a shorter nose with upward tip rotation, were included in the study. Values of preoperative and desired nasolabial angle (from morphed images), and the derived columellar–labial angle were documented. Nasal tip rotation was set to the derived angle and maintained using cock-up alar cartilage flaps. The outcome was evaluated by digital measurements of the nasolabial angle and patients’ feedback by Rhinoplasty Outcome Evaluation (ROE) score. Results Satisfactory tip rotation and an aesthetic supratip area could be achieved. The difference in preoperative and postoperative nasolabial angles was statistically significant (p value < 0.0001). The difference in desired and the obtained nasolabial angle was not significant (p value 0.085). The results were maintained on subsequent follow-up. Conclusion Application of angles in practice and use of K-wire template helps us achieve accurate and consistent results. Cock-up flap is an effective technique—to obtain an open nasolabial angle and a desirable supratip region by making use of tissues otherwise discarded.